A review of TSHR- and IGF-1R-related pathogenesis and treatment of Graves’ orbitopathy - Cui, Xuejiao; Wang, Futao; Liu, Cong (Frontiers in Immunology, 2023)
Graves’ orbitopathy (GO) is an organ-specific autoimmune disease. The pathogenesis of GO is unclear. There are few review articles on GO research from the perspective of target cells and target antigens. A systematic search of PubMed was performed focusing mainly on studies published after 2015 that were associated with the role of target cells, orbital fibroblasts (OFs) and orbital adipocytes (OAs), target antigens, thyrotropin receptor (TSHR) and insulin-like growth factor-1 receptor (IGF- 1R), and their corresponding antibodies, TSHR antibodies (TRAbs) and IGF-1R antibodies (IGF-1R Abs) in the pathogenesis of GO and the potentially effective therapies for GO that target TSHR and IGF-1R. This review suggests that OFs may be from bone marrow-derived CD34+ fibrocytes. In addition to CD34+ OFs, CD34- OFs are important in the pathogenesis of GO and may be involved in hyaluronan formation. CD34- OFs expressing Slit2 suppress the phenotype of CD34+ OFs. β-arrestin 1 can be involved in TSHR/IGF-1R crosstalk as a scaffold. The study of TRAbs has gradually shifted to TSAbs, TBAbs and the titre of TRAbs, but the existence and role of IGF-1R Abs are still unknown and deserve further study. Basic and clinical trials of TSHR-inhibiting therapies are increasing, and TSHR is an expected therapeutic target. Teprotumumab has become the latest second-line treatment for GO. This review aims to effectively describe the pathogenesis of GO from the perspective of target cells and target antigens and provide ideas for the fundamental treatment of GO.